2023
DOI: 10.1186/s12957-023-03147-x
|View full text |Cite
|
Sign up to set email alerts
|

Ideal marker for targeted axillary dissection (IMTAD): a prospective multicentre trial

Jan Žatecký,
Oldřich Coufal,
Ondřej Zapletal
et al.

Abstract: Background Targeted axillary dissection (TAD) is an established method for axillary staging in patients with breast cancer after neoadjuvant chemotherapy (NAC). TAD consists of sentinel lymph node biopsy and initially pathological lymph node excision, which must be marked by a reliable marker before NAC. Methods The IMTAD study is a prospective multicentre trial comparing three localisation markers for lymph node localisation (clip + iodine seed, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The search yielded 98 articles, of which 6 met the inclusion criteria, encompassing 574 patients ( Table 1 ; Figure 2 ) [ 13 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search yielded 98 articles, of which 6 met the inclusion criteria, encompassing 574 patients ( Table 1 ; Figure 2 ) [ 13 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of RSL in TAD is often referred to as the MARI (marking the axillary lymph node with radioactive iodine seeds) procedure (Figure 1). [13].…”
Section: Introductionmentioning
confidence: 99%
“…Response assessment with MRI was reported to be compromised in 15 of 151 patients (9.9%). Furthermore, in the prospective IMTAD study 86 , which included 189 patients, marking with a 125 I seed (135 patients), magnetic marker (30), or carbon suspension (24) after NST in a clipped TLN are being compared. Recently published results demonstrated comparable complication rates regarding marker placement and localization, and marker dislodgement.…”
Section: Discussionmentioning
confidence: 99%
“…TAD consists of the combination of SLNB and targeted lymph node biopsy (TLNB), that is, the removal of the most suspicious malignant lymph node which resulted in being metastatic prior to NACT. Numerous and different marking systems have been developed to label lymph nodes for eventual TAD: positive axillary nodes could be marked by metallic clips, usually in titanium, radioactive, or magnetic seeds, and radar reflectors and radiofrequency markers or carbon particles through their ultrasound (US)-guided insertion in the selected lymph node before chemotherapy [41,44,86]. During surgery, target lymph nodes can be revealed by different systems, such as imaging (usually intra-or preoperative US) or specific probes based on the chosen marker [52].…”
Section: Alternative Techniques and Strategies Proposed To Minimize S...mentioning
confidence: 99%
“…In order to minimize the SLNB FNR in patients with axillary involvement, different techniques and strategies have been proposed (e.g., TAD by marking biopsy-positive lymph nodes prior to NACT with various tools such as carbon suspension, metallic clip, radioactive or magnetic seeds, radar reflectors, and radiofrequency markers, the use of a dual tracer, or the removal of at least three lymph nodes) [41][42][43][44][45]. To date, the prognostic significance of these strategies has not been sufficiently investigated, but some studies have demonstrated, and confirmed with follow-up data, that the SLNB is neither related with an increased recurrence rate in axilla, nor with a worsened disease-free survival (DFS) or OS [5,[46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%